Effective treatment of threatening hemoptysis by ultraselective embolization: Experience of 50 cases - Brazzini, Augusto (2019)
Fifty patients with diagnosis of threatening hemoptysis, 35 men and 15 women were referred for minimally invasive management. Tuberculosis and its sequela were the most frequent causes. Prior angiography, 41 were subjected to arterial embolization, which was successful, six needed additional embolization and four required two extra embolizations; embolization was not performed in one because there was not active bleeding. There were no complications. Therefore, arterial embolization in these cases is a safe procedure and can save lives.